Evaluasi Pelaksanaan Alokasi Dana Desa (ADD) di Bidang Ekonomi - Imam, Sadrul; Daaris, Yuli Yanti (Lembaga Yasin AlSys, 2023)
Indonesia is one of the countries in the form of an organization, so its scope is very broad. This country was formed aims to improving the welfare oas mentioned in the opening UUD 1945 Constitution. According to Law Number 72 of 2005 chapter I paragraph II it states: